THE PROBLEM OF CONSTITUTIONALISM OF VILLAGE HEAD TENURE IN THE DIMENSION OF THE STATE OF LAW AND DEMOCRACY - Muchlisin Alfarabi (DE RECHT (Journal of Police and Law Enforcement), 2024)
The research in this journal is entitled "The Problem of Constitutionalism of Village Head Tenure in the Dimension of the State of Law and Democracy". The request for an extension of the term of office of the village head is difficult because, although legally the problem is an open policy that can be used to make political laws, it is contrary to the ideals of Democracy which demands that power remain under control. The research conducted uses statutory (statute upproach) and conceptual (conceptual approach) approach techniques  as part of normative Law research methodology. The findings of this study show that, in contrast to the tenure of regional heads and presidents and vice presidents, the 1945 NRI Constitution does not specifically limit the term of village heads. This is one of the factors that contribute to this variation of regulation inseparable. In the view of the State, Law and Democracy both allude to aspects of abuse of power when there is a longer period of power in the government structure.